Ta Derniere Marche Dans La Mosquee - Abu-Usayd, Ubaydah; Hedjoudje, Abderrahmane (Canada France, 2018)
The film documents events after the Quebec City mosque brutal terrorist attack on January 29th, 2017, when a lone shooter entered the Centre Cultural Islamique de Québec (CCIQ) in Sainte-Foy, Quebec and began shooting. Six men were killed, 19 more were injured in the first such attack at a place of worship on Canadian soil.
Verzio Film Festival Submission
Keywords: Documentary films